Sick Day Management for Adults with Diabetes Who Take Insulin - Nancy Gal; Linda B. Bobroff (EDIS)
When people have type 1 or type 2 diabetes and take multiple daily insulin injections, their blood glucose levels can rise drastically due to a cold or another minor illness. This can result in serious health problems. The best way for people with diabetes to prevent a minor illness from becoming a major illness is to have a personalized sick day plan designed with their health care provider before they become ill. This 4-page fact sheet is a major revision that discusses ways in which illness affects diabetes control, development of a sick day plan, times to call your health care provider, checking blood glucose and urine ketones, medicines, and diet.